Breast cancer and abortion: collaborative reanalysis of data from 53 epidemiological studies, including 83?000 women with breast cancer from 16 countries. - Beral, V; Bull, D; Doll, R; Peto, R; Reeves, G (2004)
BACKGROUND: The Collaborative Group on Hormonal Factors in Breast Cancer has brought together the worldwide epidemiological evidence on the possible relation between breast cancer and previous spontaneous and induced abortions. METHODS: Data on individual women from 53 studies undertaken in 16 countries with liberal abortion laws were checked and analysed centrally. Relative risks of breast cancer--comparing the effects of having had a pregnancy that ended as an abortion with those of never having had that pregnancy--were calculated, stratified by study, age at diagnosis, parity, and age at first birth. Because the extent of under-reporting of past induced abortions might be influenced by whether or not women had been diagnosed with breast cancer, results of the studies--including a total of 44000 women with breast cancer--that used prospective information on abortion (ie, information that had been recorded before the diagnosis of breast cancer) were considered separately from results of the studies--including 39000 women with the disease--that used retrospective information (recorded after the diagnosis of breast cancer). FINDINGS: The overall relative risk of breast cancer, comparing women with a prospective record of having had one or more pregnancies that ended as a spontaneous abortion versus women with no such record, was 0.98 (95% CI 0.92-1.04, p=0.5). The corresponding relative risk for induced abortion was 0.93 (0.89-0.96, p=0.0002). Among women with a prospective record of having had a spontaneous or an induced abortion, the risk of breast cancer did not differ significantly according to the number or timing of either type of abortion. Published results on induced abortion from the few studies with prospectively recorded information that were not available for inclusion here are consistent with these findings. Overall results for induced abortion differed substantially between studies with prospective and those with retrospective information on abortion (test for heterogeneity between relative risks: chi2(1) =33.1, p<0.0001). INTERPRETATION: Pregnancies that end as a spontaneous or induced abortion do not increase a woman's risk of developing breast cancer. Collectively, the studies of breast cancer with retrospective recording of induced abortion yielded misleading results, possibly because women who had developed breast cancer were, on average, more likely than other women to disclose previous induced abortions.